Analytical Solution for the Frictional Anisotropy of a Corrugated Fault - Martin P. J. Schöpfer; Conrad Childs (Geophysical Research Letters)
Abstract Fault surfaces exhibit anisotropic roughness, with elongate ridges and grooves aligned in the slip direction. When inactive faults are reactivated under a new stress regime, induced by natural processes or human activities, the maximum resolved shear stress is likely to act obliquely to inherited surface corrugations increasing the fault shear strength. Analytical solutions for the shear strength of a corrugated fault, idealized as a frictional serrated surface of infinite extent separating rigid blocks under any shear stress direction, have been derived. The solutions show that the shear strength increases with increasing angle between the corrugation axes and the shear stress direction, and with fault roughness. Further, the fault slip direction may deviate significantly from the maximum resolved shear stress direction toward the corrugation axes. Finally, the reactivation potential does not only depend on stress state, fault orientation and friction, but also on surface roughness and the orientation of the corrugations.